A redescription of the rare eucyclopine copepod Eucyclops productus Kiefer, 1939 (Multicrustacea: Copepoda: Cyclopoida: Cyclopidae) and a keу to Eucyclops subgenera and species of China and adjacent areas - Ding, Ruirui; Chen, Feizhou; Alekseev, Victor R. (Zootaxa, 2022)
The rare freshwater copepod Eucyclops (Speratocyclops) productus Kiefer, 1939 from Lake Mandongco, Tibet Autonomous Region, China, is redescribed. This species was originally found and described from a pond south of Chushul village, and many of the details did not meet modern standards for describing the species. In this paper, the morphological characteristics of this species are described in detail and compared with other members of the subgenus Speratocyclops species recorded in China. The key features of the species are: 1) long caudal rami, 2) the coxal seta of the fourth pair of legs armed with long hairs in the proximal part and short denticles in the distal part, 3) the inner spine of the fifth pair of legs long and strong. An identification key to 22 species of Eucyclops known from China and adjacent areas is also provided.